Long-Term Effect of β-Blocker Use on Clinical Outcomes in Postmyocardial Infarction Patients: A Systematic Review and Meta-Analysis - Liang, Chunling; Zhang, Chenhao; Gan, Shibao; Chen, Xiaojie; Tan, Zhihui (Frontiers in Cardiovascular Medicine, 2022)
Background: Prior studies provided inconsistent results regarding long-term effect of β-blocker use on clinical outcomes in post-myocardial infarction (MI) patients. Methods: We searched for articles regarding long-term effect of β-blocker use on clinical outcomes in patients after MI and published before July 2021 in the databases as follows: PubMed, Web of Science, Medline, EMBASE and Google Scholar. STATA 12.0 software was used to compute hazard ratios (HRs) and their 95% confidence intervals (CIs). Results: The study indicated that β-blocker group had significantly lower long-term all-cause mortality, cardiovascular mortality, major adverse cardiac events (MACE) in post-MI patients, compared to no β-blocker group (all-cause mortality: HR, 0.67; 95% CI: 0.56-0.80; cardiovascular mortality: HR, 0.62; 95% CI: 0.49-0.78; MACE: HR, 0.87; 95% CI: 0.75-1.00). The study indicated no significant long-term effect of β-blocker use on risk of hospitalization for heart failure (HF), risk of recurrent MI, risk of stroke and risk of repeat revascularization in post-MI patients (risk of hospitalization for HF: HR, 0.82; 95% CI: 0.58-1.16; risk of recurrent MI: HR, 0.93; 95% CI: 0.78-1.11; risk of stroke: HR, 0.94; 95% CI: 0.79-1.12; risk of repeat revascularization: HR, 0.91; 95% CI: 0.80-1.04). Conclusions: The meta-analysis demonstrated significant long-term effects of β-blocker use on all-cause mortality, cardiovascular mortality and risk of MACE in post-MI patients, whereas no significant long-term effect was showed on risk of hospitalization for HF, risk of recurrent MI, risk of stroke and risk of repeat revascularization in post-MI patients.